Clinical Medicine Research (Clinical and Experimental Biomedicine,, 2018)
This book presents an update on new trends and developments in broadly defined medical disciplines. The reader will learn about a whole range of multidisciplinary topics, regarded as being important for advancing the understanding of disease pathogenicity, diagnostic methods, and patient management. These topics include a holistic approach to physiotherapy, with proprioceptive neuromuscular facilitation at the core of it. Furthermore potential ways to protect kidneys during ischemic coronary interventions, and psychosocial aspects in cancer survivors are discussed. Other topics deal with growth hormone deficiency in short children and responses of molecular markers of bone metabolism to growth hormone replacement therapy. In addition the modern use of transcranial laser-induced photobiomodulation showing surprising benefits in autism disorder is presented. The expert contributions take on the challenges presented to medical professionals by ever growing medical knowledge and various individual and contextual issues that require a multidisciplinary approach in patient management. The authors present bench-to-bed clinical research to make useful additions to the knowledge on contemporary diagnostic procedures, therapy, and quality of life of patients. The book aims to provide stimulus for new research ideas and to give new perspectives on practical clinical issues. The book is intended for primary care clinicians, family physicians, medical scholars, and other clinicians who treat and manage patients.